Homeopathic solutions induce production of winged forms in aphid - Mapeli, Nilbe Carla; Da Silva, Gustavo Ferreira [UNESP]; Santos, Ricardo Henrique Silva; Cremon, Cassiano; Chamma, Larissa [UNESP]; Luperini, Bruno Cesar Ottoboni [UNESP] (Lepidus Tecnologia, 2022)
The aphids control (Brevicoryne brassicae L.) in kale (Brassica oleracea L. var. acephala) is one of the main challenges for its production. This obstacle becomes greater in agroecological production systems. Thus, the objective of this study was to verify the formation of winged individuals in colonies of B. brassicae aphids, when exposed to kale treated with homeopathic solutions. The treatments were resistant 5CH, susceptible attacked 5CH, aphid nosode 30CH, and the controls that are water (without dynamization) and distilled water + 70% ethanol 5CH, being applied every day for 15 days. Kale plants were inoculated with aphids and irrigated using homeopathic solutions. After 15 days of inoculation, the plants were removed from the bag and the number of winged forms and nymphs of B. brassicae was counted. Homeopathic preparation Resistant 5CH provided a smaller number of winged individuals and a larger number of nymphs per colony. The plants treated with the susceptible attacked 5CH homeopathy showed a higher number of winged aphids, but a reduced number of nymphs. Aphid nosode 30CH treatment was promising to Brevicoryne brassicae control in kale plants, as it induced polymorphism, presenting a greater number of winged aphids and a reduced number of nymphs per colony.
Keywords: Brassica oleracea; Brevicoryne brassicae; ecological control; homeopathy; kale